Pesticide Residue in Foods : Sources, Management, and Control - Khan, Mohidus Samad; Rahman, Mohammad Shafiur (Springer International Publishing : Imprint: Springer, 2017)
This book presents an in depth study of different aspects of pesticide use in food production. The text covers the sources of pesticide residues in foods, relevant health and environmental concerns, degradation of pesticides after their use, and available laws and regulations to regulate pesticide use. In addition, different pesticide management techniques, such as: reduction of pesticide residues in grains and foods, alternatives to conventional pesticides, and prospects of organic farming are also covered. Pesticide Residue in Foods: Sources, Management, and Control aims to raise awareness of the proper use of these chemicals in order to lower residue in foods and reduce risk for consumers.